Effect of nickel niobate B-site precursors on phase formation, microstructure and dielectric properties of perovskite PNN ceramics - S. Ananta (2018)
Relaxor perovskite lead nickel niobate (PNN) ceramics were fabricated by using B-site precursor method, in which both columbite-NiNb2O6and corundum-Ni4Nb2O9were separately employed as nickel niobate B-site precursors. It has been found that optimization of sintering condition can successfully lead to highly dense and pure PNN ceramics in both routes. Between the two B-site precursor routes, pure perovskite PNN ceramics with slightly better densification and dielectric properties can be produced by using the columbite-route. © 2008 World Scientific Publishing Company.